Neurofunctional assessment at term equivalent age can predict 3‐year neurodevelopmental outcomes in very low birth weight infants. (4th December 2015) - Picciolini, Odoardo; Montirosso, Rosario; Porro, Matteo; Giannì, Maria L.; Mosca, Fabio
Abstract: Aim: Preterm infants are at high risk of developing motor delay, learning difficulties and behavioural problems and the availability of valid neurodevelopmental assessments is a major clinical issue. This study evaluated the relationship between preterm infants' neurofunctional assessment at term equivalent age and neurodevelopment outcome at three years of chronological age. Methods: Neurofunctional assessment was performed in 70 very low birth weight infants at term equivalent age and neurodevelopmental outcome was assessed at three years of chronological age with the Griffiths Mental Development Scale – Extended Revised. Results: At term equivalent age, 81% of the children had normal neurofunctional scores and 82.5% of those showed normal neurodevelopmental outcome at three years. Of the 19% who had impaired development at term equivalent age, 38.5% had neurodevelopmental delay at three years. Impaired neurofunctional status was associated with an increased risk of developmental delay in the global quotient (odds ratio 12.1) and locomotor sub‐quotient (odds ratio 18.35) compared with normal neurofunctional status. Infants with sepsis or necrotising enterocolitis also faced a higher risk of neurodevelopmental delay. Conclusion: Neurofunctional assessment performed at term equivalent age appeared to provide early identification of preterm infants at risk of neurodevelopmental delay at three years of chronological age.